Standardization Research on SF6 Mixed Gas and Eco-Friendly Alternative Gas Equipment - Yanmiao HE; Yin HUANG; Xianglian YAN; Zhibing LI (Zhongguo dianli)
In order to support the "dual carbon" goals, adapt to the requirements of limiting the use of SF6 gas, and enhance the environmental friendliness of power grid equipment, research on the standardization of SF6 mixed gas and eco-friendly alternative gas equipment is conducted. Based on the current status of eco-friendly gas equipment research and application, the technical standards of SF6/N2 mixed gas equipment were reviewed. A standardization framework was established covering equipment materials, operation and maintenance, test and detection, instruments and meters. For eco-friendly alternative gas C4F7N equipment replacing SF6, a standardization framework was constructed, including gas performance detection technology and method, equipment operation and maintenance, test and detection, and recycling. Based on this, a standard system of SF6 mixed gas and eco-friendly alternative gas equipment was preliminarily proposed, consisting of six sub-branches consistent with the standard system of GIS equipment in power industry, reflecting the research direction of eco-friendly gas equipment standardization.